2015
DOI: 10.1007/s00264-015-2835-2
|View full text |Cite
|
Sign up to set email alerts
|

Which AO/OTA 31-A2 pertrochanteric fractures can be treated with a dynamic hip screw without developing a lateral wall fracture? A CT-based study

Abstract: AO/OTA 31-A2 pertrochanteric fractures with a lateral wall height of > 1.68 cm and an anterior component of > 2.10 cm in circumference are not likely to sustain a lateral wall fracture when treated with a DHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…A recent CT-based study concluded that a height of <16.8 mm is associated with a higher incidence of intraoperative lateral wall fractures in patients with AO/OTA A2 pertrochanteric fractures treated with DHS. 27 We demonstrated that the threshold height of 20.445 mm is a reliable predictor of iatrogenic lateral wall fractures when using CMNs. When the height is less than this value, surgeons must be aware of the higher risk of iatrogenic lateral wall fractures and pay more attention to surgical procedures and implants that can help to avoid such fractures.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A recent CT-based study concluded that a height of <16.8 mm is associated with a higher incidence of intraoperative lateral wall fractures in patients with AO/OTA A2 pertrochanteric fractures treated with DHS. 27 We demonstrated that the threshold height of 20.445 mm is a reliable predictor of iatrogenic lateral wall fractures when using CMNs. When the height is less than this value, surgeons must be aware of the higher risk of iatrogenic lateral wall fractures and pay more attention to surgical procedures and implants that can help to avoid such fractures.…”
Section: Discussionmentioning
confidence: 71%
“…An intraoperative lateral wall fracture was defined as the presence of new fracture lines or bone defects occurring at the lag screw insertion site or lateral displacement of a fracture fragment on the postoperative CT image. 27 The vastus ridge is the watershed of cortical and cancellous bone. To evaluate the height of the fractures, we marked the point at which the fracture line started from the lateral cortex and then measured the distance from this point to the vastus ridge on a plain pelvic radiograph (Figure 1(a)).…”
Section: Radiological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Other studies confirm that unstable fractures resulting in lateral wall compromise should be submitted to a combined surgical treatment, not only with DHS, for better functional outcomes. 9 10 Computed tomography is another option that is considered more reliable for the measurement of the lateral wall thickness, 11 but it is not part of the routine evaluation in our service due to its high cost and lower feasibility compared to X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…8 Outros trabalhos comprovam que em fraturas instáveis e com consequente comprometimento da parede lateral o tratamento cirúrgico deve ser combinado, e não isolado com DHS, para melhores resultados funcionais. 9 10 A tomografia computadorizada é outra opção considerada mais fidedigna para a mensuração da espessura da parede lateral, 11 porém não compõe a avaliação de rotina em nosso serviço, devido aos altos custos e à menor praticidade quando comparada às radiografias.…”
Section: Discussionunclassified